Automated flow-injection method for cadmium determination with pre-concentration and reagent preparation on-line - Di Nezio, Maria Susana (2005)
The spectrophotometric determination of Cd(II) using a flow injection system provided with a solid-phase reactor for cadmium preconcentration and on-line reagent preparation, is described. It is based on the formation of a dithizone-Cd complex in basic medium. The calibration curve is linear between 6 and 300 μg L-1 Cd(II), with a detection limit of 5.4 μg L -1, an RSD of 3.7% (10 replicates in duplicate) and a sample frequency of 11.4 h-1. The proposed method was satisfactorily applied to the determination of Cd(II) in surface, well and drinking waters.